Charge inhomogeneity of carbon. (29th December 2020) - Liang, Z F; Luo, Y Q; Xue, H T; Tang, F L; Fan, D; Yao, X J
Abstract: Charge distribution on every atom of carbon matter in four dimension forms (cluster, fullerene, atomistic carbon chain, nanotube, graphene, surface and solid) was investigated by the first-principles calculation. It is found that the charge distribution in most of these materials is inhomogeneous, even in one certain solid phase. We found that if one atom in carbon has different surrounding environment from another one nearby, they always have electron transfer, that is, they have different charge. In round C10 ring, C24 and C60 fullerenes, charge is zero, while charge is not zero in pentagon C10 ring, C30 and C70 fullerenes. At the ends of atomistic chains, nanotube or on the edges of graphenes, carbon atoms have larger positive or negative charge, while almost zero in the central parts. Charge is zero in diamond and graphite, while it is not zero in the high pressure solid phase hexagonite or on some carbon surfaces. The non-zero charge in carbon possibly means its non-zero valence.